Transformation of cadmium tetracyanoquinodimethane (TCNQ) into a cadmium terephthalate metal-organic framework - Sohail, Manzar; Kiani, Farooq Ahmad (Australian journal of chemistry, 2017)
The transformation of cadmium 7,7,8,8-tetracyanoquinodimethane (TCNQ) into a cadmium terephthalate co-ordination polymer is reported, with the chemistry of this material elucidated using elemental analysis, X-ray photoelectron spectroscopy and synchrotron radiation single-crystal X-ray diffraction. A heptacoordinated CdII linear coordination polymer catena-poly[triaqua-(μ2-benzene-1,4-dicarboxylato-κO,O′)cadmium(ii)]hydrate (1) was isolated while attempting to recrystallize Cd(TCNQ)2. Density functional theory calculations for the oxidation of benzylic carbon attached to the cyano group provided evidence that the reaction pathway proposed herein is highly exergonic and thermodynamically plausible. This structure showed a distorted pentagonal bipyramidal geometry together with a symmetrical mononuclear unit in which each CdII ion is doubly bridged by a dicarboxylato anion. Owing to the softness and minute size of these crystals, this structure had to be elucidated using synchrotron radiation X-ray crystallography.